Put Your Shoes On - Dunbar, Polly ([Place of publication not identified] : Candlewick Press (MA), 2025)
Josh and Mom are heading out to Aunty Nelly's birthday party, and it's time for Josh to put on his shoes. But Josh is in his own little world, and the more Mom begs him to put his shoes on, the wilder his imagination becomes. Filled with humor and winsome illustrations, Polly Dunbar's one-of-a-kind story--brilliantly showcasing her young son's artwork as clues to what's going on in Josh's mind--speaks to the universal struggle around getting ready to leave the house, a scenario both children and caregivers can relate to.
new kids book 2025 summer.
Keywords: Birthday parties; Shoes; Imagination